Epidemiological characteristics of dogs with dental calculus: 392 cases (2012-2020) - Anna S. Spirina; Olga A. Spirina; Vladislav S. Bychkov; Aleksey M. Ermakov (RUDN Journal of Agronomy and Animal Industries)
Dental calculus is a local irritant to adjacent soft tissues, causing an inflammatory response that contributes to the development of periodontal diseases. Mineralized plaque contains bacterial toxins, which can lead to systemic infections. A retrospective analysis of the oral cavity condition of 392 dogs with dental calculus admitted for a comprehensive dental examination and oral sanitation to the Dentalvet veterinary center in 2012-2020 was conducted. An analysis of epidemiological data was performed to determine the risk factors for dental calculus formation. The study showed that small breed dogs aged 1 to 5 years were included in highrisk group for periodontal diseases. Tables with data on dental plaque and calculus indices, age characteristics of dogs, number of dog groups by skull type and breed, photographs and intraoral X-rays were provided.